IMPLEMENTING ONE NATION, ONE UNIFORM: A PROPOSAL FOR UNIFORM DRESS CODE IN INDIAN SCHOOLS - Jaishree Sahu, Siddharth Kumar Sahu, Venudhar Routiya (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This research paper explores the feasibility and potential impacts of implementing a uniform dress code policy, termed "One Nation, One Uniform," in Indian schools. The initiative aims to promote national unity, equality, discipline, and inclusivity among students across the country. Given the diverse socio-economic and cultural landscape of India, the policy's implementation raises several important considerations and challenges. This study synthesizes qualitative and quantitative data from stakeholder feedback, including students, parents, educators, and policymakers, to provide a comprehensive analysis of the potential benefits and drawbacks of the proposed uniform dress code.